1995
DOI: 10.1007/bf00190544
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Cu-sites doping on electrical properties of La2CuO4 as thermoelectric material

Abstract: The electrical conductivity and thermoelectric power for solid solutions of La2Cu0.gM0.104 (M = Mn, Fe, Co and Ni) prepared by polymeric precursor synthesis were measured between 300 and 1173 K to test its suitability as a thermoelectric material. Fe-, Mn-and Ni-doped compositions exhibited a metal-semiconductor transition with decreasing temperature, whereas Co doping showed a semiconducting behaviour in the entire temperature range of measurement. With Cu-sites doping in La2CuO4, power factors were not enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…YBa 2 Cu 3 O 7À δ , to best of our knowledge, has the highest reported ZT value (0.6 at 300 K) of the high-temperature Cu-based superconductors [18], although this result requires further verification [19]. La 2 CuO 4 has a large Seebeck coefficient of 340 μV/K at room temperature [15,17], and several groups have investigated the TE properties of La 2 CuO 4 doped with various elements [20][21][22]. Most of those reports have focused on the high temperature TE properties of these materials.…”
Section: Introductionmentioning
confidence: 92%
“…YBa 2 Cu 3 O 7À δ , to best of our knowledge, has the highest reported ZT value (0.6 at 300 K) of the high-temperature Cu-based superconductors [18], although this result requires further verification [19]. La 2 CuO 4 has a large Seebeck coefficient of 340 μV/K at room temperature [15,17], and several groups have investigated the TE properties of La 2 CuO 4 doped with various elements [20][21][22]. Most of those reports have focused on the high temperature TE properties of these materials.…”
Section: Introductionmentioning
confidence: 92%
“…Besides the oxygen vacancy contribution, the doping stoichiometry, especially that of the doping site, may significantly contribute to the electrical resistivity. Seok et al 17 observed a doping‐induced decrease of the electrical conductivity in 1 at.% transition metal (Fe/Mn/Ni/Co) doped La 2 CuO 4 . This work also reported an interesting fact that the temperature dependence of the electrical conductivity experiences a metal‐semiconductor transition for Fe‐, Mn‐, and Ni‐doped La 2 Cu 0.9 M 0.1 O 4 , 17 while no transition occurs in Co‐doped species 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Seok et al 17 observed a doping‐induced decrease of the electrical conductivity in 1 at.% transition metal (Fe/Mn/Ni/Co) doped La 2 CuO 4 . This work also reported an interesting fact that the temperature dependence of the electrical conductivity experiences a metal‐semiconductor transition for Fe‐, Mn‐, and Ni‐doped La 2 Cu 0.9 M 0.1 O 4 , 17 while no transition occurs in Co‐doped species 17 . Seok et al 17 attributed the distinction to the low spin configuration of Co 3+ , in comparison with high spin states for other metals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations